2007
DOI: 10.1007/978-3-540-73614-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Dark DNS Behavior

Abstract: Abstract. Security researchers and network operators increasingly rely on information gathered from honeypots and sensors deployed on darknets, or unused address space, for attack detection. While the attack traffic gleaned from such deployments has been thoroughly scrutinized, little attention has been paid to DNS queries targeting these addresses. In this paper, we introduce the concept of dark DNS, the DNS queries associated with darknet addresses, and characterize the data collected from a large operationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…Note that the top 4 records are the same for the entire 3 months period. Further, in contrast with the results in 2007 by [15], that found that ANY records scored only 0.0199% of the entire perceived records, we record 52.23% as observed on the darknet space. As a result, we can safely assume that the recent trend of DNS amplification attacks are behind the increase of ANY records found on the darknet in the current year [4].…”
Section: ) Query Type Distributioncontrasting
confidence: 99%
“…Note that the top 4 records are the same for the entire 3 months period. Further, in contrast with the results in 2007 by [15], that found that ANY records scored only 0.0199% of the entire perceived records, we record 52.23% as observed on the darknet space. As a result, we can safely assume that the recent trend of DNS amplification attacks are behind the increase of ANY records found on the darknet in the current year [4].…”
Section: ) Query Type Distributioncontrasting
confidence: 99%
“…Attacks to the DNS infrastructure are inferred in [30], by analyzing significant changes in the distribution of conforming and non-conforming packet sizes under the cross entropy metric. Basic statistics of DNS queries are investigated in [31] through association with 'dark' (i.e., unused) address spaces and the development of honeydns, a tool that complements existing honeypots to prevent attackers from easily evading monitored networks. Basic statistics of DNS queries are investigated in [31] through association with 'dark' (i.e., unused) address spaces and the development of honeydns, a tool that complements existing honeypots to prevent attackers from easily evading monitored networks.…”
Section: Related Literaturementioning
confidence: 99%
“…A honeynet is used to collect bot-binaries which penetrate the botnets (Freiling et al, 2005;Abu Rajab et al, 2006;Stinson and Mitchell, 2007). There are different techniques to capture bots in honeynets (McCarty, 2003;Freiling et al, 2005;Abu Rajab et al, 2006;Dagon et al, 2006;Barford and Yegneswaran, 2007;Oberheide et al, 2007;Cremonini and Riccardi, 2009;Jing et al, 2009;Szymczyk, 2009;Rieck et al, 2010;Pham and Dacier, 2011). However, intruders developed novel methods to overwhelm honeynet traps (Kugisaki et al, 2007;Wurzinger et al, 2009).…”
Section: Taxonomy Of the Botnet Detection Phenomenonmentioning
confidence: 96%